الريف وإدارة الوقت وعلاقته بالسلطة الحضرية والتنمية - البلالي, أحمد (University of Eloued جامعة الوادي, 2016)
يمثل الريف والسلطة الحضرية موضوعات متداخلة بشكل حميم، ولكن بطريقة غاية في التعقيد، فالريف هو القاعدة الاجتماعية الأساسية المساهمة فعليا في تطور المجتمع العربي من خلال خدمة الأرض التي تعتبر الرمز الحي والدائم للريفيين، ولكن بهدم البيئة الزراعية هدم لشخصية المجتمع العربي ولهويته الثقافية، ولذلك تميز الريف بمجاله الصعب، وفي المقابل تمثل المدينة المجال السعيد ببنية تحتية وحياة اقتصادية نشيطة اتّخذت الاستغلال الاقتصادي صبغة للضرائب والجباية وتمكّنت الدّولة من السيّطرة على آخر معاقل التمرّد الرّيفي وأخضعت السكان بواسطة التّثبيت ومدّ شبكة الدّولة العسكرّية والإداريّة، كما كانت القوى الريفيّة في إطار الحركة الوطنية قوى ضغط استعملتها النّخبة السياسيّة الحضرية في الفترة الاستعمارية لتجني الثمرات السيّاسية ولتفرض برامجها، فقاتل "الفلاّق" ليحصد رجل السيّاسة الحضري النّتائج. إضافة إلى عدم استغلال الوقت الحر في الأرياف نتيجة لغياب المؤسسات التنشيطية وإلى التوزيع اللامتكافئ للسلطة والتنمية وتغير بذلك هياكل التشغيل خاصة في الريف من خلال النزوح إلى المدينة وانتشار البطالة وتراجع العمل في الفلاحة وتطورت مظاهر التبعية للمدينة Both the rural areas and urban authority are intimately intertwined issues. However, the countryside has always been the social basis which contributes to the evolution of the Arab society. The rural areas have been considered a permanent living icon of the rustic community .Therefore, devastating the agricultural zone leads to the destruction of the Arab society's personality along with its cultural identity .Consequently, we deduce the clear difference between the city and the countryside; while the former represents the happier area, with its infrastructure and active economy , the latter just remained administratively and militarily under comprehensive control of state. Besides, during colonial period, the national movement involved rural people in the fight to gain freedom However, the political harvest was not in favour of the countryside and hence the selfishness of the politician managed to overwhelm rural countrymen’s patriotism. Furthermore, people in the countryside have no means of entertainment. Not only have they suffered unequal distribution of power but they also have not enjoyed equivalent development. Unemployment has been the main reason behind rural people’s migration to the city to seek for jobs. The decrease of farming and subordination to the city has lately become common.
The countryside’s time management in relation to urban authorities and development
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: الريف، الوقت الحر، السلطة الحضرية، التنمية